Hydroxyapaptite layer formation on titanium alloys surface using micro-arc oxidation - Adeleke, S. A.; Sopyan, Iis; Bushroa, A. R. (Asian Research Publishing Network (ARPN), 2015)
In recent years, research on titanium and its alloys had increased significantly for hard tissue replacement and dental applications due to their excellent mechanical properties such as high strength to weight ratio, low density and biocompatibility. However, there are some surface originated problems associated with titanium (Ti): poor implant fixation, lack of osseoconductivity, wear and corrosion in physiological environment. As the interaction between the implant and host bone is a surface phenomenon, surface properties play a prominent role in determining both the biological response to implant and the material response to the biological condition. To improve osseointegration of titanium with bone, hydroxyapatite (HA) has been widely used due to its close similarity to bone mineral. Promising new studies have been reported regarding coating titanium implant with HA using various surface modification techniques to improve the long term stability of titanium implants. Micro-arc oxidation (MAO) has attracted a lot of interest owing to its ability to produce a thick microporous oxide layer on titanium implants. The significant part of MAO is that HA can be incorporated in the oxide layer when processed in electrolytes containing calcium and phosphorous ions. The oxide layer containing hydroxyapatite can be subsequently increased via hydrothermal treatment. The HA produced on titanium surfaces has attractive features such as high porosity and adherent layer which facilitate good clinical outcomes. This review presents the state of the art of MAO and possible further suggestion of MAO for the production of HA on titanium implants.